<span>Solution
m = {-13, -1}</span>
Atoms and protons are tricking. they snicks and twix
Answer:
42.
Step-by-step explanation:
18/3 = 6 jars per day
6*7=42
Answer:
1) 11![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
2) 2
3) ![20\sqrt{3} + 15\sqrt{2}](https://tex.z-dn.net/?f=20%5Csqrt%7B3%7D%20%20%2B%2015%5Csqrt%7B2%7D)
4) ![53 + 12\sqrt{10}](https://tex.z-dn.net/?f=53%20%2B%2012%5Csqrt%7B10%7D)
5) -2
6) ![7\sqrt{2} - 5\sqrt{3}](https://tex.z-dn.net/?f=7%5Csqrt%7B2%7D%20%20-%205%5Csqrt%7B3%7D)
Step-by-step explanation:
1) 2
+ 3
- ![\sqrt{75}](https://tex.z-dn.net/?f=%5Csqrt%7B75%7D)
=(2 × 2
)+ (3 × 4
) - 5![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
= 4
+ 12
- 5![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
= 11![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
2) 4
-2
+ ![\sqrt{128}](https://tex.z-dn.net/?f=%5Csqrt%7B128%7D)
= (4 × 2
) - (2 × 7
) + 8![\sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B2%7D)
= 8
- 14
+8
= 2
3) 5
- 3![\sqrt{18} + 4 \sqrt{72} +2\sqrt{75}](https://tex.z-dn.net/?f=%5Csqrt%7B18%7D%20%2B%204%20%5Csqrt%7B72%7D%20%20%2B2%5Csqrt%7B75%7D)
= 5×
- 3×
+ 4×
+ 2×![5\sqrt{3}](https://tex.z-dn.net/?f=5%5Csqrt%7B3%7D)
= ![10\sqrt{3} - 9\sqrt{2} +24\sqrt{2} +10\sqrt{3}](https://tex.z-dn.net/?f=10%5Csqrt%7B3%7D%20-%209%5Csqrt%7B2%7D%20%2B24%5Csqrt%7B2%7D%20%2B10%5Csqrt%7B3%7D)
= ![20\sqrt{3} + 15\sqrt{2}](https://tex.z-dn.net/?f=20%5Csqrt%7B3%7D%20%20%2B%2015%5Csqrt%7B2%7D)
4) ![(2\sqrt{2} + 3\sqrt{5} )^{2}](https://tex.z-dn.net/?f=%282%5Csqrt%7B2%7D%20%20%2B%203%5Csqrt%7B5%7D%20%29%5E%7B2%7D)
= ![8 + 12\sqrt{10} + 45](https://tex.z-dn.net/?f=8%20%2B%2012%5Csqrt%7B10%7D%20%2B%2045)
= ![53 + 12\sqrt{10}](https://tex.z-dn.net/?f=53%20%2B%2012%5Csqrt%7B10%7D)
5) ![(1+\sqrt{3} ) (1-\sqrt{3} )](https://tex.z-dn.net/?f=%281%2B%5Csqrt%7B3%7D%20%29%20%281-%5Csqrt%7B3%7D%20%29)
= ![1 - 3](https://tex.z-dn.net/?f=1%20-%203)
= -2
6) ![(2\sqrt{6} -1) (\sqrt{3} -\sqrt{2} )](https://tex.z-dn.net/?f=%282%5Csqrt%7B6%7D%20-1%29%20%28%5Csqrt%7B3%7D%20-%5Csqrt%7B2%7D%20%20%29)
= ![2\sqrt{18}-2\sqrt{12} -\sqrt{3} +\sqrt{2}](https://tex.z-dn.net/?f=2%5Csqrt%7B18%7D-2%5Csqrt%7B12%7D%20%20-%5Csqrt%7B3%7D%20%20%2B%5Csqrt%7B2%7D)
= 2×
- 2×
- ![\sqrt{3} + \sqrt{2}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D%20%2B%20%5Csqrt%7B2%7D)
= ![6\sqrt{2} - 4\sqrt{3} -\sqrt{3} +\sqrt{2}](https://tex.z-dn.net/?f=6%5Csqrt%7B2%7D%20%20-%204%5Csqrt%7B3%7D%20-%5Csqrt%7B3%7D%20%2B%5Csqrt%7B2%7D)
= ![7\sqrt{2} - 5\sqrt{3}](https://tex.z-dn.net/?f=7%5Csqrt%7B2%7D%20%20-%205%5Csqrt%7B3%7D)
Hope the working out is clear and will help you. :)